Wind catcher research gaps on indoor air quality and thermal comfort in the tropics – a systematic analysis of implementation, challenges, and opportunities - Khalid, Asma; Dahlan, Nur Dalilah; Shahidan, Mohd Fairuz; Ahmad, Kamarul Arifin Bin; Bin Abas, Mohd Firdaus (Informa UK Limited, 2024)
Wind catchers are best known as a passive solution to wind-driven natural ventilation, influencing occupants’ thermal comfort and Indoor Air Quality (IAQ). The paper reviewed the research gap taxonomy for the wind catcher designs, their implementation, challenges, and opportunities on IAQ and thermal comfort. Eighty-six (86) references were screened using PRISMA and included in the review. Twenty-two sub-themes derived from coded nodes were analyzed in NVivo v11 according to Miles’ taxonomy of 7 research gaps. Based on the data extracted from wind catchers’ studies for 12 countries of Koppen Climate, taxonomy classification, and characteristic analysis, the research implies that green wind catchers improve IAQ and thermal comfort in the tropics. A matrix of wind catcher design innovations with IAQ and thermal comfort strategies is developed. The review identified wind catcher gaps in the population for ‘global compliance,’ practical knowledge for ‘wind catcher patents implementation,’ methodology for ‘mixed method practical approach,’ empirical studies for ‘occupancy evaluation,’ evidence for ‘wind catcher external and internal components’ and knowledge for ‘green practices.’ The methodology gap is the highest coded in windcatcher studies, with enormous potential in contemporary research for indoor and outdoor air quality and thermal comfort. The study proposed green wind catchers as a novel intervention for modern building challenges of pollution and comfort.